Design and performance analysis of a cost-effective proxy-LMA mobility management scheme in IP-based mobile networks with global mobility support. (2016) - Cho, Chulhee; Choi, Jae-Young; Cho, Jun-Dong; Jeong, Jongpil
Interlocking with a heterogeneous network is important because mobile users (MUs) who navigate on next-generation (NG) wireless networks want to be provided with undisrupted network services. Unfortunately, there have been few studies on methods of guaranteeing global mobility. To enhance global mobility and interoperability within the NG network environment, in this paper, we propose a proxy-local mobility anchor (Proxy-LMA) system, a mobile IP-based global inter-networking system. The purpose of the proposed Proxy-LMA system is to expand the boundary of mobility with respect to the existing mobility management protocols (PMIPv6 and MIPv6), in order to guarantee global mobility and interoperability within a heterogeneous network environment. The results revealed that the proposed Proxy-LMA system was more efficient than the other methods in terms of the signal cost and delay in a heterogeneous network environment such as wireless sensor networks.